Annual Plan 1971-72 Proposals Statistical Statements Punjab - Planning Commission (Planning Commission, 1971)
This Dam and Power Plant with Stage II of U.B.D.C. Hydel Scheme. 482 ft. High Core. Gravel Shell Dam across river Ravi near village Thein about 15 miles upstream of Madhopur Headworks.
Planning Department Punjab